Leflunomide-induced pulmonary arterial hypertension in a young man with nephrotic syndrome: A case report - Luo, Xiaoqin; Li, Jiang; Chen, Sisi; Luo, Jun (Frontiers in Pharmacology, 2022)
Drug-induced pulmonary arterial hypertension (PAH) has been widely reported but PAH caused by leflunomide is very rare. Here we report the case of a young man with nephrotic syndrome treated with leflunomide for 5 years before being admitted to our hospital for dyspnea. After discontinuing leflunomide treatment for 3 months, both the dyspnea and pulmonary artery systolic pressure improved. Right heart catheterization resulted in a significant decrease in pulmonary vascular resistance and pulmonary artery pressure 4 months later. Because persistent PAH can lead to right heart failure and even death, identifying and excluding the risk factors is critical; discontinuing leflunomide until a definite cause is identified is highly recommended.